Evolution of Capsaicinoids in Peter Pepper (Capsicum annuum var. annuum) During Fruit Ripening. Issue 8 (6th August 2016) - Barbero, Gerardo F.; de Aguiar, Ana C.; Carrera, Ceferino; Olachea, Ángel; Ferreiro‐González, Marta; Martínez, Julian; Palma, Miguel; Barroso, Carmelo G.
Abstract : The evolution of individual and total contents of capsaicinoids present in Peter peppers ( Capsicum annuum var. annuum ) at different ripening stages has been studied. Plants were grown in a glasshouse and the new peppers were marked in a temporal space of ten days. The extraction of capsaicinoids was performed by ultrasound‐assisted extraction with MeOH. The capsaicinoids nordihydrocapsaicin (n‐DHC), capsaicin, dihydrocapsaicin, homocapsaicin, and homodihydrocapsaicin were analyzed by ultraperformance liquid chromatography (UHPLC)‐fluorescence and identified by UHPLC‐Q‐ToF‐MS. The results indicate that the total capsaicinoids increase in a linear manner from the first point of harvest at ten days (0.283 mg/g FW) up to 90 days, at which point they reach a concentration of 1.301 mg/g FW. The evolution as a percentage of the individual capsaicinoids showed the initial predominance of capsaicin, dihydrocapsaicin, and n‐DHC. Dihydrocapsaicin was the major capsaicinoid up to day 50 of maturation. After 50 days, capsaicin became the major capsaicinoid as the concentration of dihydrocapsaicin fell slightly. The time of harvest of Peter pepper based on the total capsaicinoids content should be performed as late as possible. In any case, harvesting should be performed before overripening of the fruit is observed. Abstract : Evolution of Capsaicinoids in Peter Pepper ( Capsicum annuum var. annuum ) During Fruit Ripening G. F. Barbero*, A. C. de Aguiar, C. Carrera, Á. Olachea, M. Ferreiro‐González, J. Martínez, M. Palma, C. G. Barroso